2019
DOI: 10.1111/bcpt.13311
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptors in energy homeostasis: Physiology and pharmacology

Abstract: Despite increased awareness and intensified biomedical research efforts, the prevalence of obesity continues to rise worldwide. This is alarming, because obesity accelerates the progression of several chronic disorders, including type 2 diabetes, cancer and cardiovascular disease. Individuals who experience significant weight loss must combat powerful counter-regulatory energy homeostatic processes, and, typically, most individuals regain the lost weight. Therefore, decoding the neural mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…The mAChR subtype M1 is extensively expressed in the brain, and is highly abundant in the hippocampus (Falk et al., 2019). M1 is greatly involved in learning and spatial memory (Aronstam & Patil, 2009; Jiang et al., 2014), which had been shown to be restored following its activation in AD animal models (Fisher et al., 2003).…”
Section: Receptors For Achmentioning
confidence: 99%
See 1 more Smart Citation
“…The mAChR subtype M1 is extensively expressed in the brain, and is highly abundant in the hippocampus (Falk et al., 2019). M1 is greatly involved in learning and spatial memory (Aronstam & Patil, 2009; Jiang et al., 2014), which had been shown to be restored following its activation in AD animal models (Fisher et al., 2003).…”
Section: Receptors For Achmentioning
confidence: 99%
“…The mAChR M3 has also been suggested to play a role in AD. The receptor has been shown to be involved in a variety of processes (Aronstam & Patil, 2009; Falk et al., 2019), and as is evident from experiments in M3 KO mice, it is also important for fear conditioning and memory (Falk et al., 2019). Similar to mAChR M1, activation of M3 subtype has been shown to promote the elevation of the favorable sAPPα, instead of Aβ.…”
Section: Receptors For Achmentioning
confidence: 99%
“…Molecular cloning studies have revealed five subtypes of acetylcholine muscarinic receptors (M1R-M5R), all of which are G protein coupled receptors (Falk et al, 2019). The M3Rs are widely expressed throughout the brain and peripheral organs, including the liver and pancreas (Eglen, 2005; Falk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting MiniReview from the Kellendonk group reviews the latest data on the highly relevant topic of how the dopamine D2 receptor modulates motivated behaviour through regulation of neuronal activity in the striatal indirect pathway . Finally, the Clemmensen group has taken an exciting new look at muscarinic acetylcholine receptors and written a MiniReview about their role in energy homoeostasis . They outline that the receptors both play a direct role in energy homoeostasis via canonical brain circuits regulating appetite and indirect roles via neurocircuits regulating motivated behaviours and emotional stress.…”
mentioning
confidence: 99%
“…They outline that the receptors both play a direct role in energy homoeostasis via canonical brain circuits regulating appetite and indirect roles via neurocircuits regulating motivated behaviours and emotional stress. Muscarinic acetylcholine receptors might thus be novel drug targets for treatment of obesity and type 2 diabetes …”
mentioning
confidence: 99%